A Political Mediation Model of Corporate Response to Social Movement Activism - King, Brayden G (Administrative Science Quarterly, 2008)
This paper uses a theory of social movement outcomes, the political mediation model, to explain why certain corporations targeted by boycotts are more likely to concede to boycotters' demands. Hypotheses developed from this model predict that boycotts threaten tangible and intangible resources held by corporate targets, that these threats are transmitted indirectly through media coverage of the boycotts, that past declines in sales or reputation create opportunities for a movement to have influence, and that the level of threat posed by a boycott generates more influence when targeted against corporations that recently experienced declines in sales or reputation. Results from analyses of a sample of corporate boycotts reported in major national newspapers in the U.S. between 1990 and 2005 provide support for the political mediation model. Corporate targets of boycotts were more likely to concede when the boycott received a great deal of media attention. The effect of media attention was amplified when the corporate target previously experienced a decline in its reputation.